Perceptions of pastoral communities on cattle breed improvement: insights from Uganda’s community-based breeding scheme - Gonzaga Ssekibaala; John Ilukor; John Ilukor; Fredrick Bagamba (Frontiers in Animal Science)
This study assesses pastoral livestock-keepers’ perceptions of breed improvement based on participants in the Community Based Bull Breeding Programme (CBBP) of the Regional Pastoral Livelihood Resilience Project in Uganda (RPLRP). The RPLRP aimed to enhance the production and productivity of local cattle in terms of milk and beef yield, as well as the market value of live animals. This study sought to understand whether the project achieved its breeding objectives, the Community perceptions on the performance and productivity of crossed cattle breeds and the factors influencing community perceptions on breed improvement. To achieve this, the study employed a cross-sectional design, utilizing both descriptive statistics and multiple regression analysis to examine the demographic characteristics of farmers and their perceptions regarding the performance of crossbred offspring as outcomes of the CBBP. The findings indicate that farmers overwhelmingly perceived crossbred offspring as growing faster, producing more milk, and possessing a higher market value than offspring of local breeds of the same age. However, only about a third of the farmers view crossbred offspring as socially dominant, adaptable to local feeds, resistant to pests and diseases, possessing higher mating ability, and adaptable to the local environment compared to local breeds like Zebu. Furthermore, the analysis revealed that factors such as the age of the farmer, education level, cattle-keeping experience, weekly spraying, tethering as the main grazing method, and participation in livestock management training influence their perceptions of crossbred offspring, with some factors being specific to particular perceptions while others are more broadly applicable. This study concludes that the objectives of the breeding programme were largely achieved. From the results, we recommend integrating pasture improvement interventions into CBBPs to enhance the overall performance and productivity of cattle within pastoral systems. Additionally, it is crucial to strengthen government veterinary services by increasing the availability of veterinarians, providing access to free veterinary drugs, and implementing effective market regulation to ensure fair prices for cattle and their products. These measures will not only improve animal health and productivity but also support the long-term sustainability of the livestock sector.